Sistem Informasi Perincian Tarif Rawat Inap Berbasis Website di Puskesmas Maurole - Agustina Dianti Lero; Maria Adelvin Londa; Melky Radja (SATESI: Jurnal Sains Teknologi dan Sistem Informasi, 2022)
Currently, information systems and technology have developed very rapidly. One of the fields that are highly demanded to take advantage of developments in technology and information is the health sector. Information system is a network of procedures that are interconnected and work together to process certain data and turn it into a more useful form called information. Maurole Public Health Center is one of the health centers in the Ende district which currently still uses the conventional information system for the breakdown of inpatient rates. In providing services, puskesmas earn income from the services and facilities provided, one of which is inpatient services, where the income for these services comes from the tariffs that must be paid by inpatient service users. To be able to produce detailed information on inpatient rates, puskesmas are required to be able to carry out operational needs efficiently according to the functions carried out so that their goals are achieved by utilizing technological and information developments. The purpose of this study is that researchers want to build a website-based information system for inpatient rates. The research method used is a type of quantitative research. Data collection techniques by means of observation, interviews and literature study. The system development method uses waterfall and the test uses blackbox testing. This system can simplify and assist finance staff in the breakdown of rates to generate total costs.